Critical success factors for Public-Private Partnership (PPP) infrastructure and housing projects in Kenya. Issue 9 (4th July 2022) - Chileshe, Nicholas; Njau, Carol Wambui; Kibichii, Brian Kiptoo; Macharia, Lyn Njeri; Kavishe, Neema
Abstract: Despite the emergence of studies on critical success factors (CSFs) for public-private partnerships (PPPs) implementation within developing countries, there is a paucity of studies that examine CSFs barriers within the context of developing countries, particularly the sub-Saharan Africa (SSA) such as Kenya. This paper aims to investigate the perceptions of Kenyan public and private stakeholder's concerning the CSFs to the implementation of PPPs in infrastructure and housing projects. A quantitative approach using survey-based questionnaire is adopted. CSFs identified from literature review were empirically tested by data collected using a sample survey of 27 Kenyan stakeholders. Response data was subjected to descriptive and inferential statistics. Results show that "acceptance and support given by the community", "project feasibility", "the laws, regulations and guidelines put in place", "available financial market" and "having a well organised and committed public agency" were the highly ranked CSFs. In contrast, "effective and enough resource allocation and management", "transparency and equity in the procurement process", and "proper and efficient training of employees" were the least ranked CSFs. These findings can be used as a road-map for the successful implementation of PPPs, provides insights on the CSFs of PPPs in infrastructure and housing projects across the Kenyan construction sector.